CRL‐based ultra‐compact transfocator for X‐ray focusing and microscopy. (18th June 2019) - Narikovich, Anton; Polikarpov, Maxim; Barannikov, Alexander; Klimova, Nataliya; Lushnikov, Anatoly; Lyatun, Ivan; Bourenkov, Gleb; Zverev, Dmitrii; Panormov, Igor; Sinitsyn, Alexander; Snigireva, Irina; Snigirev, Anatoly
Abstract : A new ultra‐compact transfocator for X‐ray focusing and microscopy is presented. The device can be used to change the number of one‐ and two‐dimensional focusing compound refractive lenses by moving the individual parabolic X‐ray refractive lenses one‐by‐one independently, thus providing permanent energy and focal length tunability for a wide range of applications. Abstract : A new ultra‐compact transfocator (UCTF) based on X‐ray compound refractive lenses (CRLs) is presented. The device can be used to change the number of one‐ and two‐dimensional focusing CRLs by moving the individual parabolic lenses one‐by‐one independently, thus providing permanent energy and focal‐length tunability for scanning and full‐field X‐ray microscopy applications. The small overall size and light weight of the device allow it to be integrated in any synchrotron beamline, while even simplifying the experimental layout. The UCTF was tested at the Excillium MetalJet microfocus X‐ray source and at the P14 EMBL (PETRA‐III) beamline, demonstrating high mechanical stability and lens positioning repeatability.